Alterations of the podocyte proteome in response to high glucose concentrations - Schordan, Sandra; Schordan, Eric; Endlich, Nicole; Lindenmeyer, Maja Tamara; Meyer-Schwesinger, Catherine; Meyer, Tobias Nikolaus; Giebel, Jürgen; Cohen, Clemens David; Endlich, Karlhans; Maurer, Martin H. (Proteomics, 2009)
Diabetic nephropathy is one of the most common complications of diabetes mellitus and the leading cause of end-stage renal disease. A reduction in podocyte number has been documented in the kidneys of these patients. To identify the molecular changes in podocytes that are primarily caused by high glucose (HG) concentrations and not by secondary alterations (e.g. glomerular hypertension), we investigated the protein expression profiles in a podocyte cell line under long-term HG exposure (30 versus 10 mM for 2 wk). Proteins were separated by 2-DE, and we identified 39 different proteins in 48 spots that were differentially regulated by more than twofold in response to HG concentrations using MALDI-TOF MS and MASCOT software. These proteins belong to several protein classes, including cytoskeletal proteins and specific annexins (annexins III and VI). Downregulation of annexins III and VI by HG concentrations was confirmed by qRT-PCR, Western blot, and immunostaining, and was also observed in glomeruli of kidney biopsies from patients with diabetic nephropathy. Our data demonstrate that HG concentrations per se are sufficient to strongly modify the protein expression profile of podocytes, the analysis of which contributes to the identification of novel targets involved in diabetic nephropathy.
Online veröffentlicht: 30. September 2009
Gesehen am 13.01.2025